Pendidikan Kewarganegaraan Dalam Membentuk Generasi Muda Yang Mampu Menghadapi Tantangan Di Era Globalisasi - Sihombing, Ade Fitri; May, Bila; Anastasia Lumban Tobing, Dian Uli; Br. Ginting, Loficha Metesa; Simangunsong, Melva; Ritonga, Nadila Septiani; Rachman, Fazli (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
Citizenship Education is a scientific discipline that aims to form citizens who know and carry out their rights and obligations based on Pancasila and the 1945 Constitution. In the era of globalization, this education is becoming increasingly important for the younger generation to face challenges such as moral crises, individualism and low nationalism. Through a qualitative approach, this research examines the role of Citizenship Education in shaping nationalism and the character of the younger generation. The results show that this education can instill a spirit of nationalism, strengthen a sense of patriotism, and develop digital skills, critical thinking, and a sense of responsibility. Citizenship education also plays a role in building character based on Pancasila values to form a young generation that is ready to face global challenges.